2009
DOI: 10.1038/jhh.2009.97
|View full text |Cite
|
Sign up to set email alerts
|

Carotid atherosclerosis in elderly hypertensive patients: potential role of endothelin and plasma antioxidant capacity

Abstract: Endothelin-1 (ET-1) and oxidative stress are involved in the development of hypertension-induced cardiovascular complications. The aim of this study was to evaluate the relationship between plasma ET-1 level and plasma antioxidant capacity and carotid atherosclerosis. In 61 treated patients with hypertension (44 women, 35 diabetics, mean age 72.4 ± 7.2 years) medical histories, ambulatory blood pressure, blood tests (glucose, creatinine, cholesterol, haemoglobin A1c (HbA1c), ET-1) and common carotid artery int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Pharmacologic inhibition of the renin angiotensin-system has been proven effective in the prevention of stroke and dementia in hypertensive patients [1]. Moreover, observational studies have shown that carotid artery intima-media thickness (IMT) positively correlates with plasma ET-1 concentrations in hypertensive [49, 50] and in diabetic [51] patients, and that carotid artery IMT is positively associated with plasma ET-1 levels in young women with polycystic ovary syndrome [52]. Supporting the findings of the present study, the relationship between plasma ET-1 concentration and carotid artery IMT also appears to be dependent on plasma antioxidant capacity [50], suggesting that the deleterious vascular effects of ET-1 are partly ROS-mediated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacologic inhibition of the renin angiotensin-system has been proven effective in the prevention of stroke and dementia in hypertensive patients [1]. Moreover, observational studies have shown that carotid artery intima-media thickness (IMT) positively correlates with plasma ET-1 concentrations in hypertensive [49, 50] and in diabetic [51] patients, and that carotid artery IMT is positively associated with plasma ET-1 levels in young women with polycystic ovary syndrome [52]. Supporting the findings of the present study, the relationship between plasma ET-1 concentration and carotid artery IMT also appears to be dependent on plasma antioxidant capacity [50], suggesting that the deleterious vascular effects of ET-1 are partly ROS-mediated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, observational studies have shown that carotid artery intima-media thickness (IMT) positively correlates with plasma ET-1 concentrations in hypertensive [49, 50] and in diabetic [51] patients, and that carotid artery IMT is positively associated with plasma ET-1 levels in young women with polycystic ovary syndrome [52]. Supporting the findings of the present study, the relationship between plasma ET-1 concentration and carotid artery IMT also appears to be dependent on plasma antioxidant capacity [50], suggesting that the deleterious vascular effects of ET-1 are partly ROS-mediated. Whether interfering with the vascular activity of ET-1 can prevent age-induced carotid artery disease and the increased risk for stroke and cognitive impairment associated with it awaits future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, plasma antioxidant capacity can potentially affect the oxidative stress in the peripheral tissues. Moreover, it was previously reported that carotid atherosclerosis was associated with the reduced serum antioxidant capacity (Skalska and Grodzicki ). Accordingly in this study, decreased plasma antioxidant capacity may be an indicator of increased oxidative stress in the basilar artery, the latter which leads to structural and functional impairment.…”
Section: Discussionmentioning
confidence: 94%
“…Extensive preclinical and clinical studies, mainly with ET A receptor antagonists, have shown excellent therapeutic benefits in disease such as pulmonary hypertension [9], heart failure [10], atherosclerosis [11], systemic hypertension [12], chronic renal failure [13] and solid tumors [14]. These results indicate endothelin receptor antagonists, especially those selective for the ET A receptor subtype, may constitute a novel and potentially important class of agents for the treatment of the aforementioned pathological conditions.…”
Section: Introductionmentioning
confidence: 96%